Metabolic Profile of Four Selected Cathinones in Microsome Incubations: Identification of Phase I and II Metabolites by Liquid Chromatography High Resolution Mass Spectrometry - Lopes, Beatriz T.; Caldeira, Maria João; Gaspar, Helena; Antunes, Alexandra M. M. (Frontiers in Chemistry, 2021)
Consumption of synthetic cathinones, the second largest class of new psychoactive substances (NPS) reported worldwide, represents a serious public health risk. One of the biggest challenges created by the rapid spread of NPS on the illegal drug market is the discovery of selective biomarkers for their detection in biological matrices, which is only possible through the study of their metabolic profile. The synthetic cathinones 4’-methyl-N,N-dimethylcathinone (4-MDMC), 4’-methyl-N,N-diethylcathinone (4-MDEC), 4’-chloro-α-pyrrolidinovalerophenone (4Cl-PVP) and 4'-chloroethylcathinone (4-CEC) are NPS recently seized in Europe, and, to the best of our knowledge, their metabolic profiles are yet to be determined. With the ultimate goal of overcoming this gap, these cathinones were incubated in vitro in human and rat liver microsomes in the presence of Phase I and II (glucuronidation) co-factors, using α pyrrolidinovalerophenone (α PVP) as positive control. The metabolite identification was performed by liquid chromatography coupled to tandem high resolution mass spectrometry (LC-HRMS/MS). This allowed the firsthand identification of multiple Phase I and glucuronide metabolites of the selected cathinones. Additionally, a new glucuronide conjugate, derived from the recreational drug α PVP, was herein identified for the first time. Importantly, we have demonstrated that 4-MDMC and 4-MDEC can act as prodrugs of the controlled substances 4-MMC and 4-MEC, respectively. The metabolites herein identified are expected to play an important role not only by acting as potential selective biomarkers of the intake of the synthetic cathinones selected for this study but also to understand their potential adverse effects and link these causative agents to toxicities, thereby helping in the treatment of non-fatal intoxications.